Analisis Permasalahan dalam Pelaksanaan Pendidikan Inklusi di Sumatera Utara - Aura Meriska; Endang Aristianti Gultom; Rosenta L Sirungkir; Wike Afsari Sinaga; Cindy Jelita Sari; Inge Irawati; Rivandi Anju Gurning; Lili Tansliova (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The implementation of inclusive education in Indonesia aims to provide educational facilities and services for children with special needs (ABK). Inclusive education has been implemented in various schools, especially in big cities, but still faces various challenges in its implementation. This study aims to describe the problems faced by schools that provide inclusive education in North Sumatra and their resolution efforts. The objects in this study include public schools and special schools that integrate inclusive education. This study uses a qualitative approach, with data collection techniques through interviews, observations, and documentation. The data obtained are explained through the process of data reduction, data presentation, and drawing conclusions. Various problems arise, ranging from the lack of number and competence of special guidance teachers (GPK), difficulties for students in following lessons, lack of school readiness to run inclusive programs, to limited facilities and infrastructure that do not support the needs of children with special needs (ABK). In addition, low cooperation between schools, education offices, and parents is also an obstacle to the implementation of effective inclusive education.